EDUCATION OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS IN CRISIS CONDITIONS - Atamanchuk, Nina (SWorld-Ger Conference proceedings, 2023)
Current problems of higher education students’ education in crisis conditions are characterized. Strategies that can facilitate the learning process of student youth in a state of crisis are highlighted. The expediency of using art techniques as a means o